Knowledge of Therapeutic Communication among Nurses in Maternal Wards at Hospital - Huda Abdulsattar Yahya,; Hanaa Hussein Mikhlif, (AlQalam Journal of Medical and Applied Sciences, 2024)
The study aimed to assess nurses' knowledge of therapeutic communication in maternal wards at Mosul Hospitals. A descriptive study was designed and selected of a purposive sample of 100 nurses. The tool consists of demographic data from six variables and therapeutic communication from twelve questions with three answers. The study was performed in four hospitals from November 2023, April 2024. A statistical analysis uses the SPSS (26) to determine nurses' knowledge of therapeutic communication among nurses.the study results were found through descriptive statistics. Most of nurses (65%) represented moderate knowledge among nurses. A study finds a relationship between age, experience years, with their knowledge. More than half of nurses have an average knowledge of therapeutic communication. There is need to increase nurses' knowledge about therapeutic communication by providing educational program according therapeutic communication with patients. هدفت الدراسة الى تقيم معارف الممرضات حول التواصل العلاجي في ردهات النسائية في مستشفيات الموصل ز تم استخدام تصميم الدراسة الوصفية. تم اختيار 100 ممرضة مشاركة كعينات الأداة هي الاستمارة المتكونة من المعلومات الديموغرافية من ست متغيرات واسئلة حول معارف الممرضات عن التواصل العلاجي والتي تتكون من احدى عشر سؤال في ثلاث اختيارات ز الدراسة كانت في أربع مستشفيات من الشهر نوفر 2023 الى شهر ابرل 2024 وتم التوصل الى نتائج الدراسة من خلال الإحصاء الوصفي معظم الممرضات بنسبة 65 بالمئة يملكون معارف عن التواصل العلاجي مع المرضى. واوصت الدراسة على زيادة معارف الممرضات عن التواصل العلاجي بواسطة تقديم البرامج التثقيفية حول التواصل العلاجي